(untitled) (Experimental biology, 2018)
To determine associations of miRNA and mRNA of their target genes, binding characteristics of miRNA and mRNA of candidate genes of four subtypes of the breast cancer have been studied. Half of candidate genes of the triple-negative subtype had binding sites for several miRNAs. mRNA of ATM gene had seven binding sites for miR-5095, miR-619-5p, miR-5096, miR-5585-3p, miR-1273a, miR-1273g-3p, all of which bind in the 3’UTR. mRNA of AXL gene, the tyrosine kinase receptor, had binding sites for five miRNAs that are localized in 3’UTR, CDS, and 5’UTR. From five miRNA, miR-1908-3p may the most effective regulated the expression of protooncogene CBL. mRNA of СЕАСАМ5 gene contained binding sites of miR-5095, miR-619-5p, miR-5585-3p with a high degree of complementarity. mRNA of F2RL1, IAPP genes have binding sites predominantly for miR-5095, miR-619-5p, miR-5585-3p, miR-5096. Based on the obtained data, it is necessary to control the expression of candidate genes of the triple-negative subtype with miR-5095, miR-619-5p, miR-5585-3p, miR-5096 and miR-1273a, miR-1273e, miR-1273g-3p. A high free binding energy was detected for pairs of miR-6089 and triple-negative subtype RUNX1 and SFN candidate genes mRNA. mRNA of IL11, MAGEA10 and STMN1 genes had binding sites of miR-619-5p and miR-1273a, miR-1273d, miR-1273e, miR-1273f. mRNA of the subtype her2 candidate genes ADAM17, AURKA and BRCA2 strongly bind miR-619-5p. mRNA of BRIP1 gene has sites for miR-1285-5p, miR-5095, miR-619-5p, miR-5585-3p, miR-1273a, miR-1273g-3p. mRNA of CDK6 gene has binding sites for miR-548 family and multiple sites for miR-466. The presence of such binding sites in mRNA of CDK6 gene several times increases the probability of its interaction with these miRNAs. The key candidate gene ERBB3 of the her2 subtype interacts with miR-619-5p with high complementarity. 12 miRNAs can bind to mRNA of MAZ gene, binding sites are located in 5’UTR and CDS. mRNA of candidate genes of the subtype luminal A, B can bind: HMGA2 gene - five miRNA, MAPT gene - six miRNA, SMAD3 gene - four miRNA, TGFB1 gene - six miRNA. mRNA of TGFB1 and SMAD3 genes had four and three effective miR-6089 binding sites, respectively. A special feature of candidate genes of the subtype luminal A, B is the absence in their mRNA binding sites of the unique miRNA family miR-1273 and group miR-5095, miR-619-5p, miR-5585-3p, miR-5096, miR-1285-5p.